Production of high expressing A20/DAF‐ transgenic pigs on a GGTA1‐KO background. (March 2014) - Ahrens, Hellen E.; Petersen, Bjoern; Petkov, Stoyan; Herrmann, Doris; Frenzel, Antje; Hauschild‐Quintern, Janet; Lucas‐Hahn, Andrea; Hassel, Petra; Ziegler, Maren; Baars, Wiebke; Schwinzer, Reinhard; Niemann, Heiner
<x xml:space="preserve">Abstract</x> Background Pig‐to‐human xenotransplantation is promising to ameliorate the worldwide shortage of suitable human donor organs. The transplantation of xenografts evokes severe immunological rejection responses. Different approaches led to considerable progress in this respect: transgenic expression of human complement regulatory proteins such as human decay‐accelerating factor (hCD55), membrane co‐factor protein (hCD46, MCP) or hCD59 and/or knockout of the porcine α1, 3‐galactosyltransferase gene (GGTA1‐KO) prevent the hyperacute rejection response (HAR) [1, 2]. Moreover, human anticoagulant and/or anti‐apoptotic and anti‐inflammatory transgenes, such as human A20 (hA20) and human heme oxygenase‐1 (hHO‐1), could protect porcine xenografts from being rejected by the acute vascular rejection response [3, 4]. Recently, we produced pigs transgenic for hA20 which provides cytoprotective properties in porcine aortic endothelial cells in vitro [5]. However, hA20 was expressed only at low levels in heart, skeletal muscle and porcine aortic endothelial cells. Here, we generated a new tri‐cistronic hA20/hCD55/Puro vector based on the Sleeping Beauty system (kindly provided by Dr. Zoltán Ivics) and transfected it into porcine GGTA1‐KO cells that served as donor cells for somatic cell nuclear transfer (SCNT). Methods We co‐transfected GGTA1‐KO [6] porcine fibroblasts with a tri‐cistronic cDNA expression vector coding for hA20/hCD55/Puro and the SB transposase 100X plasmid. The advantage of this vector is a stable genomic integration without any plasmid‐based vector backbone and the combined integration of all transgenes at a single genomic locus which avoids transgene segregation after mating. Following puromycin selection (5 μg/ml), cells were screened by PCR for genomic integration of the vector and used for SCNT. Results In total, 1, 028 embryos were transferred to 13 recipients of which five remained pregnant. Two pregnancies were in too early stages for ultrasound diagnosis at the time of writing. One pregnancy was terminated on day 25 of gestation and eight fetuses were obtained. The hA20 mRNA levels of these fetuses were increased 21‐ to 44‐fold compared to another line (hA20/hHO‐1/GGTA1‐KO) and even higher than in the first generation hA20 transgenic pigs. Preliminary immunofluorescence analysis data showed delta mean fluorescence intensities (MFI) for hCD55 (hCD55 MFI minus control antibody MFI) of 1, 016 in average in transgenic fibroblasts in comparison to delta MFI 299 in HUVECs and 114 in PBMCs. The susceptibility of the cells to NK cell‐ and T cell‐mediated cell death compared to wild‐type fibroblasts will be determined in a 51chromium release assay. Three gilts are expected to deliver piglets in November of this year. The expression and organ distribution of hA20 and hCD55 will be characterised subsequently. Conclusions Our goal is the production of multi‐transgenic pigs with an increased expression of xeno‐relevant transgenes. The combination of ubiquitous, high expression of anti‐apoptotic and‐inflammatory transgenes such as hA20 together with a complement regulatory protein like hCD55 on a GGTA1‐KO background has the potential to prolong the survival of porcine grafts after pig‐to‐primate xenotransplantation. References [1] Phelps CJ, Koike C, Vaught TD, et al. Production of alpha 1, 3‐Galactosyltransferase‐Deficient Pigs. Science. 2002; 299: 411–4. [2] Cowan PJ, Aminan A, Barlow H, et al. Renal xenografts from triple‐transgenic pigs are not hyperacutely rejected but cause coagulopathy in non‐immunosuppressed baboons. Transplantation. 2000; 69: 2504–2515. [3] Bach FH, Ferran C, Hechenleitner P, et al. Accommodation of vascularized xenografts: expression of "protective genes" by donor endothelial cells in a host Th2 cytokine environment. Nat Med. 1997; 3: 196–204. [4] Petersen B, Ramackers W, Lucas‐Hahn A, et al. Transgenic expression of human heme oxygenase‐1 in pigs confers resistance against xenograft rejection during ex vivo perfusion of porcine kidneys. Xenotransplantation 2011; 18: 355–368. [5] Oropeza M, Petersen B, Carnwerth J W, et al. Transgenic expression of the human A20 gene in cloned pigs provides protection against apoptotic and inflammatory stimuli. Xenotransplantation 2009; 16: 522–534. [6] Hausschild J, Peterssen B, Santiago Y, et al. Efficient generation of a biallelic knockout in pigs using zinc‐finger nucleases. Proc Natl Acad Sci U S A 2011; 108: 12013–12027.